Relação entre módulos de elasticidade de peças estruturais e de corpos de prova de madeiras tropicais - Lanini, Tamiris Luiza Soares (Universidade Federal de São Carlos, 2018)
In terms of sustainability and civil construction, wood, a natural, renewable and easily obtainable material, has a good relation between resistance and density, and due to its versatility, it is an excellent alternative for employment. Therefore, the Brazilian legislation regulating wood structures projects establishes assumptions and calculation methods for the design of structures, as well as the test methods for obtaining the physical and mechanical properties of the material. It should be noted that the determination of strength and stiffness properties is based on test specimens of small dimensions and free of defects that may differ from structural parts and directly affect the performance of projected structures, as evidenced by studies applied to planted forest woods (Pinus sp. And Eucalyptus sp.). Thus, the objective of this study was to investigate the equivalence between the modulus of elasticity obtained from test specimens of small dimensions and free of defects and of parts with the aid of the tests of static flexion and transverse vibration and analysis of variance. (Caryocar villosum Aubl.) and Peroba Mica (Aspidosperma polyneuron Müll.), were studied in the study of five tropical wood species: Caixeta (Simarouba amara Aubl.), Tauari (Couratari spp.), Cambará (Erisma uncinatum Warm. Arg.), Distributed in the resistance classes of the hardwood group. At the significance level of 5%, it was verified: reliability to the transverse vibration method to obtain the modulus of elasticity (p-value 0.647); equivalence of the means between modulus of elasticity in the static flexion and in the compression parallel to the fibers of structural parts and specimens (p-value of 0.767 and 0.308, respectively). Therefore, the moduli of elasticity obtained through the tests of static bending and parallel compression to the fibers in specimens can be considered as properties of structural parts.
Relation between elastic moduli of structural parts and specimens of tropical hardwoods
Keywords: Estruturas de madeira; Rigidez; Madeiras de florestas nativas; Vibração transversal; Structures of wood; Rigidity; Woods of native forests; Transverse vibration; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS; ENGENHARIAS::ENGENHARIA CIVIL